Defect generation and annihilation in 3C-SiC-(001) homoepitaxial growth by sublimation - Hens, Philip; Müller, Julian; Wagner, Günter; Liljedahl, Rickard; Spiecker, Erdmann; Syväjärvi, Mikael (2013)
In this paper we present an investigation on the defect generation and annihilation during the homoepitaxial growth step of cubic silicon carbide by sublimation epitaxy on templates grown by chemical vapor deposition on silicon substrates. Several structural defects like stacking faults, twins and star-defects show opposite evolution from the template layer into the sublimation grown material. While single planar defects tend to annihilate with increasing layer thickness, the defect clusters assigned to the star-defects are enlarging. These issues contribute to a balance of how to achieve the best possible quality on thick layers. © (2013) Trans Tech Publications, Switzerland.
Keywords: 3C-SiC; AFM; Defects; Homoepitaxy; Sublimation; TEM; XRD